Kaedah pengukuran indek keboleh-selenggaraan berdasarkan reka bentuk untuk pemasangan (DFA) - Satu kajian kes - Ahmad Baharuddin Abdullah,; Amti Samad,; Zaidi Mohd Ripin, (2006)
Maintenance generally conducted in order to extend lifecyle of the product or system. Maintainability can be described as the measure of maintenance operation efficiency, which depends on location and condition of the targeted parts. In terms of time, the faster maintenance could be completed the better. Beside that there are several factors that should also be considered including the accesability dan location of the parts and the fasteners used. The objective of this study is to improve the present maintainability index measurement methods. Here, the Design for Assembly is used as a guideline to produce the assembly criteria. The result from the study indicated that, assembly have a great impact to the maintainability and there are a tremendous improvement